Direct measurement of AC electrokinetics properties and capture frequencies of silicon and silicon–germanium nanowires. (5th December 2017) - Merhej, M; Honegger, T; Bassani, F; Baron, T; Peyrade, D; Drouin, D; Salem, B
Abstract: The assembly of semiconductor nanowires with nanoscale precision is crucial for their integration into functional systems. In this work, we propose a novel method to experimentally determine the real part of the Clausius–Mossotti factor (CMF) of silicon and silicon–germanium nanowires. The quantification of this CMF is measured with the nanowires velocities in a pure dielectrophoretic regime. This approach combined with a study on the connected nanowires alignment yield has led to a frequency of capture evaluation. In addition, we have also presented the morphology of nanowires assembly using dielectrophoresis for a wide frequency variation of AC electric fields.